Sodiation mechanism via reversible surface film formation on metal oxides for sodium‐ion batteries. Issue 8 (5th February 2021) - Portenkirchner, Engelbert; Rommel, Sebastian; Szabados, Lukas; Griesser, Christoph; Werner, Daniel; Stock, David; Kunze‐Liebhäuser, Julia
Abstract: Long term galvanostatic charge/discharge cycling of oxygen deficient, carburized and self‐organized titanium dioxide (TiO2 ) nanotubes (NTs) in sodium ion (Na) batteries (SIBs) are subject to a significant self‐improving charge storage behavior. Surface reactions upon sodiation of carburized NTs form acicular surface films that can be reversibly cycled. We show that, alongside organic species from the decomposition of the electrolyte, mainly inorganic compounds, such as Na2 O2 and Na2 CO3, are the main constituents. These components possess a characteristic acicular morphology. Na2 O2 is found to form upon sodiation and converted to NaO2 upon desodiation. This, in combination with its pseudo‐capacitive charge storage characteristics, explains the excellent rate capability measured for TiO2‐x ‐C NTs. The observed high reversibility of this surface chemistry is also essential for the fast kinetics and the high capacity retention found in the system. Our findings point to a more general Na‐ion storage mechanism, that is potentially relevant to other transition metal oxides also. Abstract : The quasi reversible formation of an acicular surface film, with Na2 O2 being the main component, leads to a significant self‐improving charge storage capacity on self‐organized titanium dioxide nanotubes in sodium ion batteries. This work unfolds the surface film composition and deconvolutes its mechanistic details. Its transformation into NaO2 is essential for achieving the observed high rate capabilities and fast kinetics.